Pakistan's role in the Organization of Islamic Conference - Nyang, Sulayman S. (Journal of South Asian and Middle Eastern studies, 1984)
Pakistan's foreign policy and Muslim solidarity, 1947-1969; Pakistan and the development of the Organization of Islamic Conference (OIC); Pakistan's place and role in the OIC and the trade and financial relations with the OIC memberstates